Reducing social inequality through the INSS’s itinerant service in the Amazon region of Rondônia - Sampaio Macedo, Saulo (Revista del CLAD Reforma y Democracia, 2025)
This article examines the impact of public social security policies on riverside communities in the Rondonian Amazon, through the PREVBarco program. PREVBarco’s itinerant service aims to provide social security services to these isolated communities, which face great distances, transportation difficulties, natural risks and geographical barriers. The study analyzes how PREVBarco contributes to reducing social inequalities between riverside communities in the Guaporé-Mamoré regions, which receive services from the program, compared to the Lower Madeira region, which does not have this service. Using a qualitative and quantitative approach, the research combines analysis of historical and contemporary data with primary data collection through questionnaires. It is based on the hypothesis that PREVBarco improves the quality of life and reduces social inequalities in the communities it serves, highlighting the need for public policies adapted to the specific reality of each community. PREVBarco promotes the socio- economic integration of vulnerable populations, increasing income and social stability in the region.